Testing for Prohibited Substances in Rural Agricultural Show Exhibits: A Twenty-Three Year Experience. Issue 6 (4th August 2021) - Schembri, Mark; Suann, Craig; Keledjian, John; McIntyre, Bradley; Lerner, Jacob; Suttie, Joseph
Abstract: The administration of prohibited substances has been used in agricultural show competitions and animal racing industries to gain unfair competitive advantages. We report the first large prospectively designed descriptive study of drug testing in four species ( n  = 1, 598) over a 23 year period. 4.7% of tested exhibits returned positive results. Commonly detected substances included legitimate veterinary therapeutics such as the sedative acepromazine and the non-steroidal anti-inflammatory phenylbutazone. Targeted testing was more likely to return a positive result than random screening (50 vs 4.7% respectively) although numbers in this targeted sample were small ( n  = 12). Random drug testing programs were successful in detecting the minority of exhibits using prohibited substances although a wide variety of drugs were found to be used. Further vigilance and research is required in an ever-changing competitive climate to remain at the forefront of detecting new medications in animal show competitions.